Outcome of Surgical Decompression of Cauda Equina Syndrome by Laminectomy and Discectomy (Delta Medical College Journal, 2020)
Background: Cauda equina syndrome (CES) is a relatively uncommon condition typically associated with a large, space occupying lesion within the canal of lumbo-sacral spines. This syndrome is characterized by varying pattern of low back pain, sciatica, lower extremity sensorimotor loss, saddle anaesthesia and bowel and bladder dysfunction.Objective: The objective of this study was to evaluate clinical and functional outcome and operative complications in case of CES who underwent surgical decompression by laminectomy and discectomy.Materials and method: This prospective interventional study was carried out at National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR) and different private hospitals in Dhaka from January 2017 to December 2019. Patients were selected on the basis of history, clinical examinations and Magnetic Resonance Imaging (MRI) findings. Patients with fracture and compression due to other than disc prolapse were excluded from the study.Results: Out of 23 patients, 18 patients (78%) were male and 5 patients (22%) were female, age ranged from 20-60 years, with the average age 37.5 years. Twenty one patients (91%) had single level and 2 patients (9%) had two level disc herniation. The mean follow up duration was 9 months (range 6-12 months). Patients were evaluated with respect to age, time to surgery and scoring system for CES before and after operation. Those who were treated within 48 hours and those after 48 hours showed significant difference in outcome (p